Writing the lost generation : expatriate autobiography and American modernism - Monk, Craig, 1969- (Iowa City : University of Iowa Press, 2008)
In Writing the Lost Generation, Craig Monk unlocks a series of neglected texts while reinvigorating our reading of more familiar ones. Well-known autobiographies by Malcolm Cowley, Ernest Hemingway, and Gertrude Stein are joined here by works from a variety of lesser-known, but still important, expatriate American writers, including Sylvia Beach, Alfred Kreymborg, Samuel Putnam, and Harold Stearns. By bringing together the self-reflective works of the Lost Generation and probing the ways the writers portrayed themselves, Monk provides an exciting and comprehensive overview of modernist expatri.
Introduction: The lost generation and the critical function of autobiography -- Beyond the sermonic tradition -- Self-aggrandizement and expatriate reputation -- Searching for a representative expatriate -- Place as a strategy of attachment -- Patterns of women's stories.
Includes bibliographical references (pages 199-207) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Autobiography -- 20th century -- History and criticism; Authors, American -- France -- Paris -- 20th century -- History and criticism; Authors, American -- Biography -- History and criticism; Expatriate authors -- France -- Paris -- 20th century -- History and criticism; Modernism (Literature); Autobiography; Autobiographie -- 20e siècle -- Histoire et critique; Écrivains américains -- France -- Paris -- 20e siècle -- Histoire et critique; Écrivains américains -- Biographies -- Histoire et critique; Écrivains expatriés -- France -- Paris -- 20e siècle -- Histoire et critique; Modernisme (Littérature); Autobiographie; autobiography (genre); LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LITERARY CRITICISM -- American -- General; Authors, American; Authors, American -- Biography; Autobiography; Expatriate authors; Modernism (Literature); France -- Paris; 1900-1999; Criticism, interpretation, etc